The limits to the operation of municipal public power in the management of water resources of Marapanim and Itacaiúnas river basin, state of Pará - Batista Cirilo, Brenda; Trindade de Almeida, Oriana (Geografares, 2020)
River basin management is closely related to land use management planning, confirming the need to adjust municipal land management with water management. In the state of Pará, aspects such as territorial extension, poor intermunicipal organization, and relative qualitative and quantitative abundance of the resource, among others, are particularities that provide greater challenges to the implementation of water resources policies, which demonstrates the importance of acting on a local level. To identify how the municipal government acts in the management of water resources, at local and intercity level, in the state, and what is its relationship with the state management body, interviews were conducted at 19 municipal environmental secretariats located in the territory of two river basins: Marapanim and Itacaiúnas, both entirely located within the state. It was found the existence of both logistical and institutional limitations of the municipal government concerning environmental management, and also concerning the performance of the state government, as a political entity, in promoting the aspects of participation and decentralization of management.
Keywords: Management. Water resources.; Municipality; Environment.; Pará - Brazil